2022
DOI: 10.3389/fmars.2021.792179
|View full text |Cite
|
Sign up to set email alerts
|

Physical Responses of Pinctada fucata to Salinity Stress

Abstract: This study was conducted to understand the changes of physiological and biochemical indexes of black and red shell Pinctada fucata under acute high and low salt stress. In this study, the salinity of 35‰ was used as the control, while the salinities of 20 and 50% salinity were used as the low and high salt treatment groups, respectively. The osmotic pressure (OSM) and ion concentration in the hemolymph, Na+-K+ -ATPase (NKA) activity and respiratory metabolism in gills, and antioxidant and immune (non) enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 55 publications
(89 reference statements)
2
18
0
Order By: Relevance
“…Its activity provides a major driving force for activating other ion transport systems involved in osmotic regulation 47 . In this study, NKA showed a U-shaped distribution with the increase of salinity, which was consistent with the results of black and red shell P. fucata after 1.5 h salinity stress 20 and red shell P.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Its activity provides a major driving force for activating other ion transport systems involved in osmotic regulation 47 . In this study, NKA showed a U-shaped distribution with the increase of salinity, which was consistent with the results of black and red shell P. fucata after 1.5 h salinity stress 20 and red shell P.…”
Section: Discussionsupporting
confidence: 91%
“…Oxygen, metabolic level and physiological status required for maintaining the lowest metabolic level of aquatic animals can be directly or indirectly re ected by it 46 . During the life activities of shell sh, respiratory metabolism re ects the physiological status, metabolic characteristics and adaptability to external environmental stress 20 . Salinity and temperature are important environmental factors affecting the respiratory metabolism of aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations